Variation in Utilization of Postoperative Rehabilitation After Total Hip Arthroplasty in Japan - Ohtera, Shosuke; Kato, Genta; Ueshima, Hiroaki; Mori, Yukiko; Nakatani, Yuka; Nakayama, Takeo; Kuroda, Tomohiro (Archives of physical medicine and rehabilitation, 2024)
•Most patients undergo inpatient rehabilitation after THA.•Outpatient rehabilitation was provided to approximately 20% of patients.•High-volume hospitals have shorter inpatient rehabilitation periods.•There are variations in the postoperative care provided after THA.•Effort to understand the causes of variation are needed in the future. The use of rehabilitation after arthroplasty in Japan is unknown. We aimed to identify utilization of postoperative rehabilitation after total hip arthroplasty (THA) and to explore the factors associated with rehabilitation usage. A retrospective cohort study using the National Database of Health Insurance Claims and Specific Health Checkups of Japan (NDB). Hospitals nationwide. Patients aged >40 years who underwent primary THA between 2017 and 2018 (N=51,332). Not applicable. The proportion of patients who underwent postoperative rehabilitation and the number of rehabilitation days were also calculated. Patient demographic characteristics, hospital case volumes, and regions associated with continuing postoperative rehabilitation were analyzed using a Cox proportional hazards model. Eligible patients were selected from 3033 hospitals, of whom 41,192 (80%) were women. Of these, 94% used inpatient rehabilitation, and 20% received outpatient rehabilitation. The mean durations of rehabilitation were 47±72 days for inpatient and 195±109 days for outpatient, respectively. Large-scale hospitals performing more than 200 procedures annually had the shortest duration of inpatient rehabilitation (36-65 days) and the longest duration of outpatient rehabilitation (220-109 days) compared with smaller hospitals. The regression model consistently showed that rehabilitation continued longer at hospitals with over 200 patients per year (HR 0.96, 95% CI 0.93-0.99, P<.007). The Japanese health care system provided higher access to inpatient rehabilitation after THA than other countries. One limitation of this study is that long-term care insurance data were not analyzed. However, outpatient rehabilitation vary according to hospital case volume. Further research is needed to determine the causes of variation in rehabilitation use and the effect of variation on patient outcomes.